Adrenal activity and anxiety-like behavior in fur-chewing chinchillas (Chinchilla lanigera) - Ponzio, Marina Flavia (2012)
Due to its complexity, in combination with a lack of scientific reports, fur-chewing became one of the most challenging behavioral problems common to captive chinchillas. In the last years, the hypothesis that fur-chewing is an abnormal repetitive behavior and that stress plays a role in its development and performance has arisen. Here, we investigated whether a relationship existed between the expression and intensity of fur-chewing behavior, elevated urinary cortisol excretion and anxiety-related behaviors. Specifically, we evaluated the following parameters in behaviorally normal and fur-chewing animals of both sexes: 1) mean concentrations of urinary cortisol metabolites and 2) anxiety-like behavior in an elevated plus-maze test. Urinary cortisol metabolites were higher only in females that expressed the most severe form of the fur-chewing behavior (P ≤ 0.05). Likewise, only fur-chewing females exhibited increased (P ≤ 0.05) anxiety-like behaviors associated with the elevated plus-maze test. Overall, these data provided additional evidence to support the concept that fur-chewing is a manifestation of physiological stress in chinchilla, and that a female sex bias exists in the development of this abnormal behavior.